1965
DOI: 10.2134/agronj1965.00021962005700030001x
|View full text |Cite
|
Sign up to set email alerts
|

Sulfur and Nitrogen Content of Alfalfa Herbage During Growth1

Abstract: Synopsis Sulfur fertilization increased the sulfur and nitrogen content and yield of alfalfa herbage. Percent sulfur was highest in the young growth and declined at a near linear rate for both deficient and nondeficient plants. The use of a critical level of sulfur in alfalfa herbage needs to be associated with a definite stage of growth. The nitrogen to sulfur ratio in the herbage was nearly constant at all stages of growth and was much narrower in the nondeficient than in sulfur‐deficient herbage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
14
0

Year Published

1969
1969
1999
1999

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 8 publications
1
14
0
Order By: Relevance
“…These figures are much lower than the 0.20-0.22% required by an actively growing ryegrasswhite clover pasture (McNaught & Crisstoffels 1961). Total S compared with (N/S), (i.e., total N % : total S %) values (Table 2) were more affected by S application, being similar to the mature lucerne results obtained by Pumphrey & Moore (1965). For lucerne, Beaton et al (1969) found a (PIS), ratio of 1.0-1.2 for most effective S sources, whereas Watson (1967) gained no response to S at a (PIS), value < I.…”
Section: Resultssupporting
confidence: 73%
“…These figures are much lower than the 0.20-0.22% required by an actively growing ryegrasswhite clover pasture (McNaught & Crisstoffels 1961). Total S compared with (N/S), (i.e., total N % : total S %) values (Table 2) were more affected by S application, being similar to the mature lucerne results obtained by Pumphrey & Moore (1965). For lucerne, Beaton et al (1969) found a (PIS), ratio of 1.0-1.2 for most effective S sources, whereas Watson (1967) gained no response to S at a (PIS), value < I.…”
Section: Resultssupporting
confidence: 73%
“…PUMPHERY and MOORE (19) found that a critical sulfur concentration changed with the growth stages of alfalfa, while a critical N:S ratio was relatively constant at all growth stages. Apparent difference in constancy ofN: S ratio between rice and alfalfa is perhaps attributed to differences in proportion of vegetative part to total dry weight and patition of nitrogen and sulfur in different plant parts.…”
Section: Critical Levels Of Tissue Sulfur Content At Different Growthmentioning
confidence: 99%
“…Total S and S04-S, both expressed as percentages of the dry matter, have been used as indexes of S sufficiency in alfalfa. Critical concentrations of total S in alfalfa (M edicago sativa L.) are dependent upon stage of development (Pumphrey and Moore, 1965), but generally group around 0.20 to 0.25% S in whole tops (Mertz and Matsumato, 1956;Ensminger and Freney, 1966;Martin and Walker, 1966;Martin and Matocha, 1973;Cornforth and Sinclair, 1982). Approximately 150 Jlg/g S04-S in the second to fourth mature leaf, and 40 Jlg/g S04-S in the midstems at the bloom stage are considered critical concentrations of S04 -S under greenhouse conditions for alfalfa ).…”
Section: Introductionmentioning
confidence: 99%